Sedimentary evolution of the Holocene subaqueous clinoform off the southern Shandong Peninsula in the Western South Yellow Sea - Qiu, J.; Liu, Jian; Saito, Y.; Yang, Z.; Yue, B.; Wang, H.; Kong, X. (2014)
Based on the stratigraphic sequence formed since the last glaciation and revealed by 3000 km long high-resolution shallow seismic profiles and the core QDZ03 acquired recently off the southern Shandong Peninsula, we addressed the sedimentary characteristics of a Holocene subaqueous clinoform in this paper. Integrated analyses were made on the core QDZ03, including sedimentary facies, sediment grain sizes, clay minerals, geochemistry, micro paleontology, and AMS 14C dating. The result indicates that there exists a Holocene subaqueous clinoform, whose bottom boundary generally lies at 15-40 m below the present sea level with its depth contours roughly parallel to the coast and getting deeper seawards. The maximum thickness of the clinoform is up to 22.5 m on the coast side, and the thickness contours generally spread in a banded way along the coastline and becomes thinner towards the sea. At the mouths of some bays along the coast, the clinoform stretches in the shape of a fan and its thickness is evidently larger than that of the surrounding sediments. This clinoform came into being in the early Holocene (about 11.2 cal kyr BP) and can be divided into the lower and upper depositional units (DU 2 and DU 1, respectively). The unit DU 2, being usually less than 3 m in thickness and formed under a low sedimentation rate, is located between the bottom boundary and the Holocene maximum flooding surface (MFS), and represents the sediment of a post-glacial transgressive systems tract; whereas the unit DU 1, the main body of the clinoform, sits on the MFS, belonging to the sediment of a high-stand systems tract from middle Holocene (about 7-6 cal kyr BP) to the present. The provenance of the clinoform differs from that of the typical sediments of the Yellow River and can be considered as the results of the joint contribution from both the Yellow River and the proximal coastal sediments of the Shandong Peninsula, as evidenced by the sediment geochemistry of the core. As is controlled mainly by coactions of multiple factors such as the Holocene sea-level changes, sediment supplies and coastal dynamic conditions, the development of the clinoform is genetically related with the synchronous clinoform or subaqueous deltas around the northeastern Shandong Peninsula and in the northern South Yellow Sea in the spatial distribution and sediment provenance, as previously reported, with all of them being formed from the initial stage of the Holocene up to the present. © 2014 Science Press, Ocean University of China and Springer-Verlag Berlin Heidelberg.